HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN TINDAKAN PENCEGAHAN DIARE PADA BALITA - Girsang, Vierto Irennius (JURNAL HEALTH REPRODUCTIVE, 2021)
Diarrhea is an endemic disease in Indonesia which has very potential for KLB followed by death. Knowledge and attitude of women who have toddler at Kelurahan Dwikora, Kecamatan Helvetia in 2018 highly influence the incidence of diarrhea in their toddler. When they havegood knowlageand positive, they will know how to prevent diarrhea early, and vice versa. Healthy behavior and healthful environment are the two methods in decreasing the death rate and complication caused by diarrhea. The objective if the research was to find out the correlation of women’s knowledge and attitude with prevention from diarrhea at Kelurahan Dwikora. The research used correlation study with cross sectional desaign. The population was 234 women at Kelurahan Dwikora and 44 of them were used as samples. The data were analyzed by using univariate analysis and bivariate analysis with chi square statistic test. The result of the research showed that there was the correlation of womens knowledge (p-value=0,003) and attitude (p-value=0,001) with the prevention from diarrhea. The conclusion was that womens good knowledge and positive attitude could influence the prevention from diarrhea. The conclusion was that women’s good knowledge and positive attitude could influence the prevention from diarrhea before their children underwent diarrhea or its relapse. It is recommended that women who have toddler increase the knowledge of preventing diarrhea by participating in counseling provided by health care providers and by asking them about accurate prevention from diarrhea.